The Digital Competitiveness of Bulgaria - 2017 - Marikina, Maria (Research Papers, 2018)
When considering the competitiveness of an economy, we understand the possibility of producing a sustainable product and increasing productivity. This competitiveness is dynamic due to rapidly changing technologies in recent years. In response to the need for assessment and the right decisions on a country’s willingness to do the best for digital technology and transformation, it is necessary to clarify the essence of Bulgaria’s digital competitiveness and to present it in a comparative perspective. This is the purpose of the study.